Extraction of Copper(I) Thiosulfate by Modified Chitosan - Anggraito, Okky; Sabarudin, Akhmad; Mulyasuryani, Ani (Chemistry Department, The University of Brawijaya, 2014)
Chitosan is one of non-toxic natural biopolymer and abundance in nature. Chitosan have two active sites such as amine and hydroxyl groups. Amine groups (-NH2) in chitosan can be modified into secondary amine (-NHR). In this research, copper was dissolved as copper(I) thiosulfate as anion complex (Cu(S2O3)23-) and chitosan was modified by trimethylamine sulfur trioxide (TMAS). One of hydrogen atom in –NH2 was substituted by –SO3Na. The result of this research, the modified chitosan was identified by FT-IR. FT-IR spectra gave characteristic band at 3600-3200 cm-1 (O-H and N-H); 1648 cm-1 (C=O); 1115,74 cm-1 (S=O) and 617,18 cm-1 (N-S). The result of surface analysis using SEM and TEM showed that the surface morphology of sulfated chitosan as a result of modification is different in comparison with chitosan. Based on chitosan, pH extraction was adjusted to pH 3 until 8. After optimum pH of extraction was obtained then re-extraction was done by using thiosulfate solution at 0.05 ; 0.10 ; 0.50 ; and 1.00 M. Extraction and re-extraction of copper(I) thiosulfate was analyzed by Atomic Absorption Spectrophotometer (AAS). The highest efficiency extraction using modified chitosan and chitosan respectively at pH 3 and 6. The efficiency re-extraction using modified chitosan and chitosan respectively 100% and below 100%.